The Roman pottery manufacturing site in Highgate Wood : excavations 1966-78 - Brown, A. E. (Archaeopress Roman archaeology ;, 2018)
Excavations at Highgate Wood, London, over a period of eight years uncovered at least ten pottery kilns, waster heaps, ditches and pits, but only a few definite structures. This volume provides a very detailed analysis of the forms and fabrics of the pottery finds.